Dynamics of Crank-Piston Mechanisms - Davitashvili, Nodar; Bakhshaliev, Valeh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This monograph focuses on the dynamical research work on crank-piston mechanisms considering basic and additional motions. In order to have full dynamical analyses of piston machines and their mechanisms, the book studies the crank-piston mechanisms with clearances in kinematic pairs. The tasks are carried out by focusing on friction, wear and impacts in mechanisms, as well as cracks formation in links and elasticity of details, with distributed and concentrated masses. Then, the reliability and durability of the mechanisms of piston machines is applied on oil and gas transportation. The monograph is meant for design specialists. It is also useful for specialists-manufacturers and designers of piston machines, scientists and lecturers, doctoral students.
Introduction -- General problem of dynamics of crank-piston mechanism with clearances in kinematic pairs -- Dynamic research of crank - piston mechanism with clearances in two kinematic pairs -- The operational characteristics (friction, wear) in kinematic pairs of crank-piston mechanisms -- Research of operational characteristics problem (cracks formation) of crank-piston mechanism -- Research of operational characteristics of crank-piston mechanism by computer engineering -- Dynamic analysis of crank-piston mechanism with consideration of impacts in kinematic pairs -- The study of cranks - piston mechanisms with taking into account the clearances and elasticity of links -- Dynamic research of crank-piston mechanism with clearances in kinematic pairs and consideration of elasticity of links with concentrated masses -- Research of kinematic and dynamic errors of crank-piston mechanisms.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Machinery; Energy harvesting; Multibody Systems and Mechanical Vibrations; Machinery and Machine Elements; Energy Harvesting